Cambios paleoambientales durante los últimos 7.000 14C años en el ecotono bosque-estepa, 47-48° S, Santa Cruz, Argentina (Ameghiniana, 2014)
Palien analysis of sediment samples from three archaeological sequences in the Parque Nacional Perito Moreno (47-48° S, Santa Cruz Provine e, Argentina) allowed the reconstruction of the last 7000 "C years of vegetation and clima te history at the Nothofagus forest-Patagonia steppe ecotone. Paleoenvironrnental reconstruction is based on comparison between fossil and modern pollen assemblages and with other environmental proxy data. Before 6500 yr BP, pollen assemblages show existence of a grass steppe with cushion plants of Empeirum rubrum, Azorella and Acaena suggesting more arid and colder conditions than today. Between 6500 and 2700 yr B.P. Asteraceae subf. Asteroideae and Nothcfagus pollen increased reflecting local establishment of the forest-steppe ecotone and indicating an increase in surnrner ternperatures and higher moisture availability. Between 2700 and ea. 2000 yr BP the open Nothofagus forest reached its maximum development indicating an episodic increase in precipitation and a decrease in temperature. Expansion of shrub steppe between 1200 and 250 yr BP suggests an increase in temperature and precipitation comparable to that of modem times. From 250 yr BP onwards, grass-steppe analogous to the modem ones, became dominant indicating an increase in moisture availability. The past plant cornmunities inferred from the pollen sequence are similar to those that currently exist in the area along a precipitation gradient from 200 to over 400 mm. The paleoenvironmental interpretation suggests that past clima tic conditions were different during the different moments of human occupation of hunter-gatherer groups who lived in this area between 7000 yr BP and the 19th century.